Pengaruh Tenaga Kerja, Tabugan, Investasi dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Provisi Bali Tahun 1996-2013 - Ratih C., I Gst. Ag. Ayu; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The economic growth in Bali has the potencial of different regions and experiented income inequality, to reduce income inequality one of them is by increasing the income output capital. The purpose of this study was to determine the effect of labor, savings, investment and government spending on economic growth. This research was conducted in the province of Bali, the data used is the time series data for 18 years from 1996-2013. The analysis technique used is multiple linear regressions. The results found that labor, savings, investment and government spending simultaneously significant effect on economic growth. Labor, savings, investment and government were spending partially positive and significant impact on economic growth.
Keywords: investment; government spending; economic growth; savings